Astrobiology and Society in Europe Today (SpringerBriefs in Astronomy,, 2018)
This White Paper describes the state of astrobiology in Europe today and its relation to the European society at large. With contributions from authors in twenty countries and over thirty scientific institutions worldwide, the document illustrates the societal implications of astrobiology and the positive contribution that astrobiology can make to European society. The White paper has two main objectives: 1. It recommends the establishment of a European Astrobiology Institute (EAI) as an answer to a series of challenges relating to astrobiology but also European research, education and the society at large. 2. It also acknowledges the societal implications of astrobiology, and thus the role of the social sciences and humanities in optimizing the positive contribution that astrobiology can make to the lives of the people of Europe and the challenges they face. This book is recommended reading for science policy makers, the interested public, and the astrobiology community.